Discussing Hitler : advisers of U.S. diplomacy in Central Europe, 1934-1941 - Frank, Tibor (Central European University Press, 2003)
This book promises to illuminate the foreign policy of the Roosevelt administration during the rise of Hitler's Germany. It is based on the heretofore unpublished notes of J.F. Montgomery (1878-1954), U.S. ambassador ("Minister") to Hungary before World War II. In Budapest, Montgomery quickly made friends with nearly everyone who mattered in the critical years of Hitler's takeover and preparation for World War II. His circle included Admiral Horthy, the Regent of Hungary, subsequent prime ministers, foreign ministers, members of both houses of parliament, as well as fellow diplomats from all over Europe. In addition, as an avid player of golf and bridge, he had an active social life that was interconnected with a large circle of influential friends in the United States. Minister Montgomery dictated the full content of each and every important political discussion to his secretary shortly after returning to his chancery in Budapest. He assiduously collected, recorded, and organized the information that he gained through these key relationships. His "Conversations" as he called them, represent an unusual depth of politically valuable information in this complex and important period of time. It is also valuable to understand how the U.S. minister representing Franklin Delano Roosevelt at the Budapest outpost came to appreciate and to some degree even share the value system of interwar Hungary. Publishing the confidential "Conversations" of Minister Montgomery, along with a selection of his correspondence, will also shed some unusual light on the perception of Hitler's ascent by the United States, and how this perception was shaped and channeled by one key U.S. diplomat